Differential Psoriatic Effect of Imiquimod on Balb/c and Swiss Mice - Salwa, Fathima; Badanthadka, Murali; D’Souza, Lidwin (Journal of Health and Allied Sciences NU, 2021)
Introduction The influence of animal strain on psoriasis model development by imiquimod (IMQ) has been studied in Balb/c and Swiss mice.Materials and Methods Female mice of either strain were challenged with 5% IMQ (62.5 mg on back skin, 10 mg on right ear). They were observed for the severity of the disease using Psoriasis area severity index (PASI), splenomegaly, and histopathological alterations. To validate the model, well-established antipsoriatic drug clobetasol (0.05%, 120 mg on the back skin, 10 mg on the right ear) was used. Additionally, to study the strain-dependent response to IMQ associated with oxidative stress, various antioxidant factors like superoxide dismutase (SOD), catalase (CT), and glutathione (GSH) were measured. Antioxidant natural product curcumin (1%, 150 mg on back skin, 12.5 mg on right ear) was used to evaluate the alleviation of oxidative stress on distinct mice strain.Results PASI score, body weight, and histopathology indicated the development of disease in both the strains, severity, and stability of which was dependent on the particular strain. Splenomegaly suggested the systemic effect, which was comparable in both the stains. IMQ and its involvement in redox status were confirmed by an alteration in the activity of SOD, CT, and levels of GSH.Conclusion This study demonstrated that, in the IMQ-induced psoriasis model, the genetic background has some impact on the disease severity, stability, and redox imbalance.
Keywords: Balb/c mice; clobetasol; curcumin; imiquimod; psoriasis; Swiss mice